The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/5187543
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Manufacturing Properties of Crack Self-Healing Capsules Using Cement Powder for Addition to Cement Composites

Abstract: We fabricated crack self-healing capsules using cement powder for mixing into cement composites and evaluated the properties of the capsule manufacturing process in this study. The manufacture of the self-healing capsules is divided into core production processing of granulating cement in powder form and a coating process for creating a wall on the surfaces of the granulated cement particles. The produced capsules contain unhardened cement and can be mixed directly with the cement composite materials because t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Spherical (Giannaros et al 2016a(Giannaros et al , 2016bKanellopoulos et al 2016Kanellopoulos et al , 2017Al-Tabbaa et al 2019;Al-Tabbaa 2019, 2020) Cementitious 8 Spherical or tubular (Sisomphon et al 2011;Formia and Irico 2015;Formia et al 2015aFormia et al , 2016Anglani et al 2020aAnglani et al , 2020bRen et al 2020b;Lv et al 2020a) PMMA, PLA, PS 8 Tubular (Hilloulin et al 2015;Araújo et al 2017Araújo et al , 2018Choi et al 2017aChoi et al , 2017bAnglani et al 2019;Rodríguez et al 2020;Wu et al 2020 (Gruyaert et al 2016;Wang et al 2016;Dong et al 2018aDong et al , 2018b Other 11 Spherical or tubular (Ge et al 2011;Van Tittelboom et al 2012;Li et al 2013Li et al , 2016aDong et al 2015;Xiong et al 2015;De Nardi et al 2017;Fang et al 2018;Souza and Al-Tabbaa 2018;Wang et al 2019a;Lv et al 2020b) sules (29 μm average diameter) under SEM (Beglarigale et al 2018), showed that the encapsulated sodium silicate was in the form of spherical solid particles inside the capsules. It was concluded that sodium silicate was consumed due to cracks on the surface of the capsules that allowed an air-drying process to take place.…”
Section: Shell Materials Number Of Papers Geometry Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Spherical (Giannaros et al 2016a(Giannaros et al , 2016bKanellopoulos et al 2016Kanellopoulos et al , 2017Al-Tabbaa et al 2019;Al-Tabbaa 2019, 2020) Cementitious 8 Spherical or tubular (Sisomphon et al 2011;Formia and Irico 2015;Formia et al 2015aFormia et al , 2016Anglani et al 2020aAnglani et al , 2020bRen et al 2020b;Lv et al 2020a) PMMA, PLA, PS 8 Tubular (Hilloulin et al 2015;Araújo et al 2017Araújo et al , 2018Choi et al 2017aChoi et al , 2017bAnglani et al 2019;Rodríguez et al 2020;Wu et al 2020 (Gruyaert et al 2016;Wang et al 2016;Dong et al 2018aDong et al , 2018b Other 11 Spherical or tubular (Ge et al 2011;Van Tittelboom et al 2012;Li et al 2013Li et al , 2016aDong et al 2015;Xiong et al 2015;De Nardi et al 2017;Fang et al 2018;Souza and Al-Tabbaa 2018;Wang et al 2019a;Lv et al 2020b) sules (29 μm average diameter) under SEM (Beglarigale et al 2018), showed that the encapsulated sodium silicate was in the form of spherical solid particles inside the capsules. It was concluded that sodium silicate was consumed due to cracks on the surface of the capsules that allowed an air-drying process to take place.…”
Section: Shell Materials Number Of Papers Geometry Referencesmentioning
confidence: 99%
“…Generally, when tubular macrocapsules are used, in most cases, the cement paste is prepared according to the standard procedure and the capsules are placed in a specific point of the mould/specimen during casting (Hu et al 2018;Van Belleghem et al 2018aTsangouri et al 2019;Anglani et al 2020b;Lv et al 2020a). A simple procedure for the calculation of the survivability ratio of macrocapsules has been proposed (Hilloulin et al 2015;Choi et al 2017a). According to this procedure, the capsules are separated from the mixture by performing a washing test, immediately after the mixing process, and the number of intact capsules is related to the original number of capsules added in the mixture.…”
Section: Mechanical Durability -Survivability During Mixingmentioning
confidence: 99%
“…In the 1990s, the first applications of cylindrical capsules in cementitious composites were investigated within a number of studies [1,2]. The capsules can be cylindrical (hollow pipettes or tubes) or spherically made with various range of materials such as glass, polymers, and even lightweight porous aggregates [3][4][5][6][7][8]. Choi et al [6] have encapsulated cement powder in a cement-based capsule and used in a mortar mixture to confirm their method.…”
Section: Introductionmentioning
confidence: 99%
“…The capsules can be cylindrical (hollow pipettes or tubes) or spherically made with various range of materials such as glass, polymers, and even lightweight porous aggregates [3][4][5][6][7][8]. Choi et al [6] have encapsulated cement powder in a cement-based capsule and used in a mortar mixture to confirm their method. In the study carried out by Sisomphon et al [9], expanded clay aggregates were impregnated by sodium monofluorophosphate solution which were then coated by cement powder.…”
Section: Introductionmentioning
confidence: 99%
“…Crystalline admixtures were also used to achieve robust self-healing [3]. Capsules were also utilized which recover damaged concrete by releasing the liquid into the cracks [4]. Fly ash (FA) can be used as a supplementary cementitious material for generating crystalline product which enhances the strength and durability of concrete as well [5].…”
Section: Introductionmentioning
confidence: 99%